Protective effect of glucan against visceral leishmaniasis in hamsters. - Cook, J A (1982)
The effect of pre- or posttreatment with glucan, a reticuloendothelial stimulant, on the course of Leishmania donovani infection was assessed in highly susceptible hamsters. Intravenous administration of glucan before or after L. donovani infection significantly suppressed proliferation of amastigote-stage parasites in liver and spleen. Glucan-activated peritoneal macrophages in vitro also significantly reduced multiplication of the intracellular parasite. Ultrastructural studies revealed a well-defined hepatic granulomatous response to glucan, with hypertrophic Kupffer cells and reduced numbers of intracellular parasites compared to the control group. In additional studies, groups of hamsters were immunized by intravenous injections of glucan with Formalin-killed promastigote-stage L. donovani cells and challenged 60 days after the last immunizing injection. This treatment regimen significantly prolonged the mean survival time of those hamsters which died after infection, relative to untreated control groups. Hamsters stimulated with the glucan-killed promastigote preparation also exhibited significant reductions in splenic amastigotes on days 10 and 21 postinfection compared with all other control groups, but on day 35, splenic amastigotes did not differ significantly from those of control animals. Our composite observations provide evidence for glucan-enhanced nonspecific resistance of hamsters to visceral leishmaniasis.